PERAN STAKEHOLDER DALAM MENINGKATKAN PARTISIPASI PEMILIH PEMULA PADA PEMILIHAN UMUM 2024 DI KABUPATEN BOJONEGORO - Kidung Bukit Darmawan; Esa Septian; Ida Suwasanti (Jurnal Ilmu Sosial dan Ilmu Politik)
The purpose of this research is to know and describe the collaborative role of stakeholders in increasing the participation of beginner voters in the 2024 general elections in the Bojonegoro district. This investigation is descriptive research with a qualitative approach by identifying five informants as research objects, namely KPU Bojoneegoro, BAWASLU Bojonegoro, Academicians, Media Time, and community figures of the subject in determination with purposive sampling techniques in joining several focuses, namely initial conditions, institutional design, facilitative leadership and process of collaboration data obtained through the process of legislative rules interview – invitations and sponsorship data related to research. The data analysis of researchers uses three stages: data condensation, data presentation and conclusion drawing. The study finds that collaborative governance plays the role of stakeholders in increasing voter participation in the 2024 general election in Bojonegoro District. It's going well even though some sectors haven't maximized its implementation, institutional design, facilitative leadership and face-to-face dialogue. There was an imbalance of power and resources in the initial conditions. Based on the results of the research, the researchers suggested that there is a regular face-to-face dialogue conducted once every two months by BAWASLU, KPU Bojonegoro and associated institutions as well as beginner voters, in order to know the problems and the steps to be taken so that the goal of increasing the participation of beginners voters in the electorate can be achieved.